Careless Talk: Social Reproduction and Fault Lines of the Crisis in the United Kingdom - Brown, Gareth (Social justice, 2012)
The article discusses social conflicts that developed in Great Britain in response to the economic crisis as of May 2013, with information on the impact of austerity policies and the public's perceived lack of political representation on the development of protest movements. Topics include an overview of significant demonstrations, movements, and social conflicts in Great Britain between 2010 and 2012, the moral and ethical aspects of the financial crisis, and an analysis of the conflicts based upon social reproduction and political economy.